Respuesta :

Answer: 1/5 or 0.2

Step-by-step explanation:

STEP 1⇒1 1/5 = 1 · 5 + 1/5 = 5 + 1/5 = 6/5

STEP 2⇒6/5 - 2/5 = 6 - 2/5 = 4/5

STEP 3⇒4/5(-3/4) = 4 ·(-3)/5 · 4 = -12/20 = -3/4

STEP 4⇒-3/5 · 3 = -3 · 3/5 · 1 = -9/5

STEP 5⇒-9/5 ÷ (-9) = -9 · 1/5 · 9 = 9/45 = 1/5

Answer:

3/320

Step-by-step explanation:

Order of operations rule require that we perform work presented inside parentheses first.  

Working from left to right:  1 1/5 -2/5 = 6/5 - 2/5 = 4/5.  Then:

[(1 1/5−2/5)·(−3/4)3]÷(−9) becomes [(4/5)·(−3/4)3]÷(−9)

Note that the quantity (4/5)·(−3/4)3 is inside the square brackets and is thus next to be done.  Assuming that by (-3/4)3 you actually meant (-3/4)³, we end up with -27/64, and thus (4/5)·(−3/4)3 becomes (4/5)(-27/64), which reduces to -27/320.  

Going back to the result [(4/5)·(−3/4)3]÷(−9) above, we replace (4/5)(-3/4)³ with -27/320:  [-27/320]÷(−9).  Here we're dividing one negative number into another, which results in a positive quotient:  3/320

ACCESS MORE